2020
DOI: 10.3389/fendo.2020.586242
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of 17β-Estradiol on Pelvic Organ Prolapse by Inhibiting Mfn2 Expression: An In Vitro Study

Abstract: ObjectiveTo assess the effects of 17β-estradiol (E2) on proliferation, apoptosis, and protein expressions of fibroblasts at different concentrations and time intervals to reveal the mechanism of E2 in the treatment of pelvic organ prolapse (POP).Study DesignThe uterosacral ligament fibroblasts were collected from seven POP patients for primary culture of fibroblasts. The culture media containing 0, 10-6, 10-7, 10-8, and 10-9 mol/L E2 were used for 24, 48, 72, and 96 h.Main Outcome MeasuresThe cells were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This may imply that the vaginal fibroblasts were stimulated to synthesize factors involved in ECM deposition and remodeling at 2% E2 concentration. It was found previously that fibroblast activity may be promoted at a certain level of exposure to E2 rather than showing a linearly increasing dose response . Even though the addition of E2 to electrospun P4HB scaffolds had not been reflected in enhanced cellular functions at the protein level, gene-level data could possibly mean in vivo enhanced tissue regeneration, healing, and increased mechanical strength with certain E2 concentrations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This may imply that the vaginal fibroblasts were stimulated to synthesize factors involved in ECM deposition and remodeling at 2% E2 concentration. It was found previously that fibroblast activity may be promoted at a certain level of exposure to E2 rather than showing a linearly increasing dose response . Even though the addition of E2 to electrospun P4HB scaffolds had not been reflected in enhanced cellular functions at the protein level, gene-level data could possibly mean in vivo enhanced tissue regeneration, healing, and increased mechanical strength with certain E2 concentrations.…”
Section: Discussionmentioning
confidence: 89%
“…It was found previously that fibroblast activity may be promoted at a certain level of exposure to E2 rather than showing a linearly increasing dose response. 48 Even though the addition of E2 to electrospun P4HB scaffolds had not been reflected in enhanced cellular functions at the protein level, gene-level data could possibly mean in vivo enhanced tissue regeneration, healing, and increased mechanical strength with certain E2 concentrations. In vitro , E2 incorporation in other electrospun scaffolds has demonstrated to increase collagen and elastin production.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in pigs, increased abundance of estrogen precursors (androstenedione and androsterone) and other forms of estrogen (estrone and 17β-estradiol) were reported in sows with high versus low POP risk ( Kiefer et al, 2021a ). Moreover, several studies in humans have suggested changes in ESR1 gene expression levels to be associated with POP risk ( Zbucka-Kretowska et al, 2011 ; Wang et al, 2020 ), as it plays a supportive role in controlling the synthesis and breakdown of collagen in the pelvic region ( Robinson and Cardozo, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding suggested that estrogen defends the muscles and fascia of the pelvic floor against the damage caused by mechanical strain such as vaginal delivery, but the protective effect diminished in postmenopausal women due to the rapid reduction of estrogen levels, which to some extent explains why POP mainly occurs after menopause. Recently, estrogen was proved to restrain the progress of POP by inhibiting the expression level of Mitofusin-2 and promoting expression of procollagens and proliferation of fibroblasts ( Wang et al, 2020 ). Moreover, estrogen is known to have a positive effect on epithelial thickness and blood flow ( Trutnovsky, 2021 ), and therefore is well accepted for prolapse-associated complications therapy.…”
Section: Discussionmentioning
confidence: 99%